Singularly perturbed stochastic systems - Korolyuk, V.S. (Український математичний журнал, 1997)
Problems of singular perturbation of reducible invertible operators are classified and their applications to the analysis of stochastic Markov systems represented by random evolutions are considered. The phase merging, averaging, and diffusion approximation schemes are discussed for dynamical systems with rapid Markov switchings.